O papel da curadoria na criação de ambientes midiáticos - Monteiro, Rodrigo dos Santos (2013)
The goal of this dissertation is to investigate the communicative potential of curation, admitting it as a critical action. The critical role of the curators has been diagnosed particularly from the growing crisis of cultural journalism over the last twenty years. The museums‟ conservators have played similar practices (CHECA, 2008), but the new creating networks have extended these actuations apart from specific institutions, broadening the discussion to other media environments. Thus, to analyze the critical actions inherent curation, I study firstly the development of curatorial practices in museums, but from an exercise in archeology (FOUCAULT, 2005); I expand the debate from interviews of those who were the first curators to act in various systems (OBRIST, 2010) and specifically in Brazil (CHAIMOVICH, 2008). The epistemological approach traced brings studies related to body (GREINER, 2008, 2010; KATZ e GREINER, 1998, 2008; HUTCHINS, 1994; LAKOFF e JOHNSON, 1999) to think about curation as an activity involves perceptual and cognitive processes. As points of analyses were made notes on some festivals of theater and dance (arts from the body), as Festival Internacional de Teatro e de Dança de Buenos Aires (FIBA) and Festival Olhares Sobre o Corpo (Uberlândia-MG), plus a more detailed evaluation of the cultural situation of Ribeirão Pires city (SP) (DUARTE, 2012). The main hypothesis of this dissertation is that a critical curation creates media environments that change the cartography of bodies and territories The information of the works are not only internalized in the body of the viewer, once he/she creates sense to what he/she sees/ hears/ fells. In this way, it is in the nexus between curation and public where new connections are created among work of art, the local context and the public. The research considers the curation as critic when it destabilizes ways of perceiving and acting in the world. To study it, I turn to bibliographies of communication, semiotics, history and art theory, philosophy and cognitive sciences. The expected result is to bring the discussion questions that consider the curation as an area where the artistic forms of communication are designed and tested